Emergency seed aid In Kenya: a case study of lessons learned - Sperling, L. (International Center for Tropical Agriculture, 2000)
This report reviews the effectiveness of seed aid in Kenya, with emphasis on the process and products of aid delivered during the Long Rains 1997 (February to June). While focusing on a single season just after a drought, it draws on a history of almost 10 years of repeated seed aid, with yet another intervention being organized as this report is being written. From an 'internal' organizational perspective, the report explores how the seed aid was managed at the community level and then puts this in the view of an 'external' perspective that examines the effects of seed aid interventions on the longer-term sustainability of Kenyan farming systems. One of the unique features of this report is its inclusion of a strong component of smallholder farmers' own assessments and reflections on the effectiveness of the seed-aid intervention.